Biodegradable small-diameter vascular graft: types of modification with bioactive molecules and RGD peptides - E. A. Senokosova; E. O. Krivkina; L. V. Antonova; L. S. Barbarash (Вестник трансплантологии и искусственных органов, 2020)
The need for small-diameter grafts for replacing the damaged area of the blood pool is still very high. These grafts are very popular for coronary artery bypass grafting. Polymeric synthetic grafts are an alternative to autografts. A promising area of tissue engineering is the creation of a biodegradable graft. It can serve as the basis for de novo generation of vascular tissue directly in the patient’s body. Optimization of the polymer composition of products has led to improved physicomechanical and biocompatible properties of the products. However, the improvements are still far from needed. One of the decisive factors in the reliability of a small-diameter vascular graft is the early formation of endothelial lining on its inner surface, which can provide atrombogenic effect and full lumen of the future newly formed vessel. To achieve this goal, grafts are modified by incorporating bioactive molecules or functionally active peptide sequences into the polymer composition or immobilizing on its inner surface. Peptide sequences include cell adhesion site – arginine-glycine-aspartic acid (RGD peptide). This sequence is present in most extracellular matrix proteins and has a tropism for integrin receptors of endothelial cells. Many studies have shown that imitation of the functional activity of the natural extracellular matrix can promote spontaneous endothelization of the inner surface of a vascular graft. Moreover, configuration of the RGD peptide determines the survival and differentiation of endothelial cells. The linker through which the peptide is crosslinked to the polymer surface determines the bioavailability of the RGD peptide for endothelial cells.